Pengaruh Kepemimpinan Terhadap Efektivitas Kerja Pegawai di Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah Palembang - Rusmaini Rusmaini (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
In this research that will be discussed is the influence of leadership and internal communication on the effectiveness of work. The objectives of the research are: (1) to know whether there is influence of leadership on work effectiveness (2) to know how big influence of leadership to work effectiveness of employee either simultant or partial. The population of this research is employees of Faculty of Science Tarbiyah and Teacher Training UIN Raden Fatah Palembang with the number of 90 people. Data collection methods used are questionnaires and documentation. Data analysis method used is descriptive analysis and the percentage of multiple linear regression analysis using SPSS for Windows Release 16. Based on descriptive analysis of the percentage obtained by the magnitude of leadership amounted to 84.24% and categorized as very good, while the degree of effectiveness of the work amounted to 78.78% including good category. Based on calculation of double linear regression analysis also obtained Fhitung equal to 17,234 with significance 0,000. Because the price of significance obtained is less than 0.05, then the regression model obtained is significant. This means that the working hypothesis (Ha) is accepted, ie there is influence of leadership on the effectiveness of work. The magnitude of the effect is 28.4% simultaneously while partially is 16% for leadership variables. Based on the results of research, leadership gives a positive effect on the effectiveness of work.